The Bed Crisis of Winter 1995-1996 In The British NHS: An Illustration of Accountability Issues - Young, Ann P (Nursing ethics, 1999)
The aim of this article is to explore the practical complexity of accountability in health care by focusing on a particular crisis affecting one NHS trust in the UK, that of insufficient beds to meet demand. It is presented through the eyes of five middle managers with nursing backgrounds. Although the focus is on their words, their expressions of distress and their awareness of conflict, these lead to a commentary highlighting some of the relationships between theory and practice, policy making and implementation, and, in the final analysis, compulsion and choice. The managers seemed to work within four main patterns of provider accountability: public, professional, pecuniary and personal. These four Ps of accountability created incompatibilities in the accountability process, but the conclusion attempts to draw the threads together to suggest a possible way forward.In order to protect confidentiality, pseudonyms are used for the NHS trust and the interviewees, and some personal details have been disguised.